Exploring investigative policing. A study of private detectives in Britain - Gill, Martin (The British journal of criminology, 1997)
Even with the recent growth of interest in private policing, very little has been written about the work of private investigators. This is surprising considering their relatively long history and undeniably high profile in popular culture. This article discusses their modern role in the context of four key issues: competence, legitimacy, relationship with the public police and future challenges in managing a diverse policing structure. It describes the services they most typically provide, identifies their principal client groups and reflects on how statutory regulation might impact upon their work. This paper aims to develop awareness of what remains one of the most obscure forms of policing and social control